Sosialisasi Pernikahan Dini di Mata Hukum dan Dampak Kesehatan Reproduksi - Risma Eka Desiyani; Windi Widia Hastuti; Ayu Safitri; Arini Dwi Irawati (Gapenas Publisher, 2022)
This paper aims to prevent efforts that have been made to educate the community and the impact of this early marriage, as well as the factors that cause it and its impact, as well as how the views of the community have an impact on the future. This services is a qualitative field services (field services). with a normative approach, sociological services shows that: 1) efforts to prevent early marriage include conducting socialization in the form of counseling about the impact of early marriage on children's future. and reproductive health impacts. Forming a movement community to stop child marriage; 2) causes of early marriage include economic factors, family, promiscuity and low levels of education have an impact on increasing the number of children dropping out of school, especially girls, violence against women, maternal and infant mortality; 3) the community responds positively to efforts to prevent violence against children that have an impact on the future; 4) the salvation of the soul is more important than the desire to inherit. So that government support is needed to further strengthen prevention efforts and understanding the community to prevent early childhood. Keywords: early marriage in the eyes of the law and the impact of reproductive health.